Quantification Methods of Construction Claims in the Audit Process: Evidence from Indonesia (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2022)
Purpose: This study aims to evaluate the quantification method of construction claims (QMCC) used in the audit process based on the damage theory framework. An accurate quantification of claims is essentially needed to avoid construction disputes. However, earlier studies are still vague in shed light on applying the most appropriate QMCC to quantify the claims that arise from a vari- ation order (VO).Method: We conduct a case study using a mixed-methods approach. Surveys were given to 39 audi- tors at various levels (team, supervisor, and coordinator) to obtain auditors’ perceptions about the relevance of the assessment criteria according to the damage theory. We analyzed the data quantita- tively using non-parametric test Kruskal-Wallis/Mann-Whitney. Furthermore, in-depth interviews were conducted to 6 auditors and 2 related parties to identify the QMCC that conforms with the damage theory. Transcripts were analyzed qualitatively using theme analysis.Finding: There is similarities in the auditors’ perception in accepting the assessment criteria accord- ing to the damage theory. Quantification of claims in the audit process requires supporting evidence and causal link. In this study, we proposed three methods that can be applied using an estimated value approach.Novelty: The QMCCs proposed have novelty in terms of contractual aspects, causality, and support- ing evidence as a basis for analysis to eliminate opportunistic behavior from the parties.